FUNGAL AND FLORAL DIVERSITY AND THREAT TO ECOLOGICAL SUCCESSION IN ZARYAN FOREST, PARACHINAR - FIRDOUS, Q; HUSSAIN, SI; KHALID, AN (Biological and Clinical Sciences Research Journal, 2023)
Parachinar exhibits a combination of flat and hilly terrains characterized by limited vegetation, biodiversity, and resource availability. The Zaryan forest is a mountain forest that begins at the base of a mountain and extends up to but does not encompass its peak. These mountains encompassed a vast plain. In this woodland, Quercus baloot is the most prevalent plant species. The sedimentary sediments present at the beginning of this forest provide clues as to how this climax community evolved. Unbelievably, it was discovered that these species are more abundant at the base of the slope and disappear as we ascend. As the region’s economy is poor, locals visit the forest more frequently to obtain wood, herbs, other bushes, and fodder to satisfy their basic needs. They have a meager income and subsist hand to mouth. Occasionally, they cut down mountains and sell them to meet their basic requirements. The region’s disputed geographical and political position prohibits tourism, despite the region’s incredible grandeur and breathtaking views. However, the hazard is alarming because this forest ecosystem requires protection. Pakistan Environmental Journalists and other wildlife organizations should take decisive actions and precautions to halt the deterioration and biodiversity loss.